Resistance to HIV Integrase Strand Transfer Inhibitors Among Clinical Specimens in the United States, 2009–2012. (21st October 2013) - Hurt, Christopher B.; Sebastian, Joseph; Hicks, Charles B.; Eron, Joseph J.
Abstract : Among 3012 patients with clinical specimens submitted for integrase resistance genotyping from January 2009 to December 2012, 15.6% harbored ≥1 "major" integrase inhibitor mutation. Intermediate or high-level dolutegravir resistance was predicted for 6.4% (41.2% of those with ≥1 major mutation). Abstract: Background.  Data on integrase inhibitor resistance come primarily from clinical trials and in vitro studies. We examined results of all clinically indicated integrase genotypic resistance tests (GRTs) performed at a US national referral lab from 2009 through 2012. Methods.  Integrase sequences and demographic data were compiled with paired protease–reverse transcriptase (PR-RT) GRT results, when available. Analyses utilized the Stanford HIV Drug Resistance Database. "Major" integrase mutations included T66AIK, E92QV, F121Y, Y143CHR, S147G, Q148HKR, and N155H; multiple accessory mutations were also assessed. Results.  Among 3294 sequences from 3012 patients, 471 patients had viruses with ≥1 raltegravir or elvitegravir resistance mutation (15.6%). Q148 and N155 pathways were equally represented (both n = 197); 84 had Y143 mutations. Q148 rarely occurred without accessory mutations (n = 3). Among 224 patients with serial integrase GRTs, 22 with baseline wild-type acquired a major mutation, after a median 224 days between tests (interquartile range, 148–335 days). Major mutations were observed to persist up to 462 days. Most (62%) had paired PR-RT results. Patients with integrase-resistant viruses were older and more likely to have PR-RT mutations (both P < .001). Among those with PR-RT data, 42 patients had 4-class resistance (2.3%). Sex, geographic region, and test year were not associated with integrase resistance. High-level dolutegravir resistance was predicted in 12% of patients with raltegravir- or elvitegravir-resistant viruses (2% of all patients). Conclusions.  Approximately 1 in 6 US patients undergoing integrase GRT for clinical decision making harbors significant resistance, with Q148 and N155 pathways equally common. Dolutegravir is likely to have full or partial activity against most variants observed.